PENGARUH DISIPLIN, STRES KERJA DAN KOMPENSASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. INDOFOOD CBP SUKSES MAKMUR - Melkyory Andronicus; Ines Sanaya; Jefri Petrus Simanjuntak (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2020)
This study examines the problems of discipline, job stress and work compensation on employee performance. The researchers conducted the research project at PT. Indofood CBP Sukses Makmur. The total population of 150 people and 30 people were taken from the rest of the population for validity and reliability testing. Theories used to support research are human resource management theories related to discipline, work stress and compensation for performance. The research method used was a quantitative approach with quantitative descriptive research type. The data collection methods were interview, distribution of questionnaires and documentation study. The analysis method used is multiple linear regression. The results showed that discipline, work stress and compensation simultaneously and partially had a significant positive effect on employee performance with a determination coefficient of 48.4%.